Religious issues and Islamic thought in contemporary world: a few reflections - Ali, Muhammad Mumtaz; Ahmad, Khalil (Pakistan Society of Religions, 2021)
This paper deals with some of the contemporary issues which are generally associated with religion especially to Islam such as radicalism, fundamentalism, extremism, terrorism, traditionalism, and reformist thought. This is by and large claimed by Western authors who deal with Islamic thought. It is contended here that this is done due to misinterpretation of Islamic texts and negligence of their proper context and improper reading of modernity especially by those scholars who are unable to recognize the scientific nature of the Quranic discourse. This paper aims to explain the validity of such claims based on the content analysis method. It is suggested here that to comprehend the true nature of Islamic thought and resolve the problems of radicalism and extremism, the scholars of Islam need to adopt the Quranic method of study and understanding. Here some aspects of that method have been highlighted.